คุณสมบัติลดคอเลสเตอรอลของสารสกัดใบย่านางในเซลล์มะเร็งลำไส้ใหญ่เลี้ยงต่อเนื่อง Caco-2 - ดวงใจ อัจฉราภรณ์; ลิ้มเพียรชอบ นันทีทิพ; ไตรศรัทธ์ ขนิษฐพร (Health Science, Science and Technology Reviews, 2015)
การศึกษามุ่งหมายไต่สวนประสิทธิภาพของสารสกัดใบย่านางต่อการดูดซึมคอเลสเตอรอลผ่านการยับยั้ง การ นำเข้าคอเลสเตอรอล การละลายคอเลสเตอรอลเป็นอนุภาคชิ้นเล็ก และการจับกรดน้ำดี การนำเข้าคอเลสเตอรอล กำหนดหาโดยกัมมันตภาพรังสีในเซลล์มะเร็งลำไส้ใหญ่เลี้ยงต่อเนื่อง Caco-2 เตรียมอนุภาคชิ้น เล็กผสมคอเลสเตอรอล ประเมินค่ากิจกรรมกรดน้ำดีใช้สารสกัดจับกับกรดทอโรคอลิก กรดไกลโคดีออกซีโคลิก และกรดทอโรดีออกซีโคลิก ใช้ คอเลสไทรามีนเป็นตัวควบคุมเชิงบวก สิ่งที่พบแสดงว่า สารสกัดใบย่านางมีศักยภาพลดการดูดซึมคอเลสเตอรอลโดย ลดการนำเข้าคอเลสเตอรอลในเซลล์มะเร็งลำไส้ใหญ่ Caco-2 ระหว่างร้อยละ 27 ถึง 43 ยิ่งกว่านั้น สารสกัดยับยั้ง การ ละลายเป็นอนุภาคชิ้นเล็กและยับยั้ง การจัดกับกรดน้ำดีต่างชนิดพิสัยร้อยละ 18.98 ถึง 45.87 และร้อยละ 26.80 ถึง 42.65 ตามลำดับ อันซึ่ง อาจส่งผลให้การดูดซึมคอเลสเตอรอลล่าช้า สิ่งเหล่านี้ให้หลักฐานวิทยาศาสตร์สำหรับคุณสมบัติ การลดคอเลสเตอรอลของสารสกัดใบย่านาง Cholesterol lowering properties of Tiliacora triandra (Colebr.) Diels leaf extract in the Caco-2 cell line Acharaporn Duangjai1*, Nanteetip Limpeanchob2, Kanittaporn Trisat2 1 Department of Physiology, School of Medical Sciences, University of Phayao, Phayao Province, 56000 2 Pharmacological Research Unit, Department of Pharmacy Practice, Faculty of Pharmaceutical Sciences, Naresuan University, Phitsanulok Province 65000 The study aimed to investigate the effect of Tiliacora triandra (Colebr.) Diels leaf extract on cholesterol absorption through inhibition of cholesterol uptake, micellar cholesterol solubility, and bile acids binding. The uptake of cholesterol was determined by radioactivity in Caco-2 cells. Cholesterol mixed micelles was prepared for cholesterol solubility study. Taurocholic acid, glycodeoxycholic acid, and taurodeoxycholic acid were evaluated the activity of extract to bind with bile acids. Cholestyramine was also used in the positive control. The finding showed that T. triandra leaf extract has a potential to decrease cholesterol absorption by reducing cholesterol uptake in Caco-2 cells between 27 to 43%. Furthermore, the extract inhibited micelles solubility and bound with bile acids in range of 18.98 to 45.87% and 26.80 to 42.65%, respectively which may result in delayed cholesterol absorption. These provided the scientific evidences for the cholesterol lowering properties of T. triandra leaf extract.